Unemployment and structural change - International Labour Office (Geneva : International Labour Office, 1962)
This report is very timely for Britain and the U.S.A.; it is also notable for the clarity and completeness of its analysis of the sources and processes of structural economic change as it affects the labour market, and of the problems such change raises. It is also notable for its rejection of a number of myths and shibboleths which commonly influence the thinking and programmes of labour and employer organizations on these matters.
Includes bibliographical footnotes.
rpm 16/04/2018
Loans
Keywords: Unemployed; Economic policy